Distribution Patterns of Meiofauna Assemblages and Their Relationship With Environmental Factors of Deep Sea Adjacent to the Yap Trench, Western Pacific Ocean - Wang, Xiaoxiao; Liu, Xiaoshou; Xu, Jishang (Frontiers in Marine Science, 2019)
Sediment samples were collected from 23 sites near the Yap Trench in the Western Pacific Ocean with a depth range of 2896 m to 7837 m. The assemblage composition, spatial distribution, and relationship with environmental variables of meiofauna were studied. A total of 17 meiofaunal taxa were identified, including free-living marine nematodes, benthic copepods, nauplii, ostracods, halacarids, kinorhynchs, cumaceans, turbellarians, cladocerans, polychaetes, oligochaetes, isopods, tanaidaceans, amphipods, tardigrades, gastrotrichs, and pycnogonids. The average abundance of meiofauna was (172.88±149.02) ind·10cm-2. Marine nematodes were the most abundant group, with an average abundance of (120.26±102.85) ind·10cm-2, accounting for 69.97% of the total meiofauna, followed by benthic copepods (36.13±48.72) ind·10cm-2, accounting for 21.04%. The horizontal distribution of meiofauna showed that the high values of meiofaunal abundance were mainly distributed in the northwestern part of the study area and correlated with high sediment organic matter content, which possibly was related to the localized topography, food sources, and hydrodynamics within this area. Vertical distribution showed that meiofauna were mainly distributed in the upper and middle sediment layer (0-6cm). Results of BIOENV showed that sediment median diameter and phaeophorbide content were the most important factors affecting meiofauna community structure. This study provides an insight into relationships of deep-sea meiofauna assemblages with environmental factors in the Western Pacific Ocean.